Mesoporous TiO2@g-C3N4 Nanostructure-Enhanced Photocatalytic Degradation of Tetracycline Under Full-Spectrum Sunlight - Lizhe Ma; Zhiyong Fang; Jieli Duan; Jin Li; Kefu Zhu; Yinlong Jiang; Bang Ji; Zhou Yang (Molecules)
TiO2 has broad prospects in reducing the safety risks posed by emerging pollutants in water environments. However, the high recombination rate of photogenerated carriers limits the activity and photon utilization efficiency of TiO2. In this study, mesoporous TiO2 (m-TiO2) and ultra-thin g-C3N4 nanosheets were composited using a hydrothermal method, with the m-TiO2 tightly and uniformly wrapped by g-C3N4. The chemical structure, elemental composition, and optical properties of the heterojunction were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), and ultraviolet-visible diffuse reflectance spectroscopy (UV-vis-DRS). The activity of the m-TiO2@g-C3N4 was evaluated by the degradation of tetracycline hydrochloride (TCH). Results showed that the heterojunction exhibited significantly enhanced reactivity compared to pure m-TiO2 and g-C3N4, with kinetic rates of TCH being 1.48 and 6.84 times that of pure m-TiO2 and g-C3N4, respectively. The TCH degradation kinetic rate varied from 0.194 min−1 to 0.026 min−1 and then decreased to 0.015 min−1 on the scale of the bandgap and the number of absorbed photons in m-TiO2@g-C3N4. Concurrently, a 10wt% doping amount of g-C3N4 significantly increased the reaction rate of photogenerated carriers in the system compared to the recombination rate, corresponding to excellent photon efficiency. Reproducibility was evaluated, and a possible degradation mechanism is proposed. This study opens new perspectives for the optimization of catalyst preparation processes aimed at enhancing photon efficiency.